The effects of temperature on embryonic development and hatching performance in lampam jawa, Barbonymus gonionotus (Bleeker, 1849) - Khalid, Nurul Najuatul Wahidah (2016)
In natural breeding, the environmental factors including temperature are naturally based on climate condition. Thermal tolerance of the embryo in the early stages is very important for survival rate as the environmental condition varies during the development stages. An experiment was conducted to study the effects of temperature on embryonic development and hatching performance in Lampam Jawa, Barbonymus gonionotus in captive environment. The experiment was conducted in wet laboratory in Department of Aquaculture. Breeding process was implemented by induced breeding technique using Ovatide hormone with the dosage of 0.4ml/kg for female and 0.2ml/kg for male. After fertilization, the eggs were distributed evenly in three different temperatures as the treatment at 22±1˚C, 27±1˚C (room temperature) for and 32±1˚C with triplicate. Water temperature was reduced to 22±1˚C by using Resun CL500 chiller and the aquariums were covered with Styrofoam to maintain the temperature. Temperature was raised up to 32±1˚C using Eheim Jager heater. The embryonic development was observed 24 hours starting from fertilization until hatched. From the observation, found that the fastest embryonic development was in 32±1˚C and slowest in 22±1˚C. The first hatching process occurs in temperature 32±1˚C at 6 hours after fertilization with low eggs mortality and it was faster compared to 17 hours in 22±1˚C with higher mortality rate. Based on the results, it show that the hatching percentage between the three treatments were significantly different. The hatching percentage were significantly highest in 32±1˚C, which is at 90.3% (p<0.05) and lowest in 22±1˚C which is 20.4%. This proves that, the embryonic development of Lampam Jawa, B. gonionotus have a higher chance to survive in a warmer water temperature.